Comparative transcriptome analysis reveals key pathways and genes involved in trichome development in tea plant (Camellia sinensis) - Chen, Lan; Tian, Na; Hu, Mengqing; Sandhu, Devinder; Jin, Qifang; Gu, Meiyi; Zhang, Xiangqin; Peng, Ying; Zhang, Jiali; Chen, Zhenyan; Liu, Guizhi; Huang, Mengdi; et al. (Frontiers in Plant Science, 2022)
Trichomes, which develop from epidermal cells, are considered as one of the important characteristics of tea plant (Camellia sinensis (L.) O. Kuntze). Many nutritional and metabolomic study studies have indicated the important contributions of trichomes to tea products quality. However, understanding the regulation of trichome formation at the molecular level remains elusive in tea plants. Herein, we present a genome-wide comparative transcriptome analysis between the hairless Chuyeqi (CYQ) with fewer trichomes and the hairy Budiaomao (BDM) with more trichomes tea plant genotypes, toward the identification of biological processes and functional gene activities that occur during trichome development. In the present study, trichomes in both cultivars CYQ and BDM were unicellular, unbranched, straight, and soft-structured. The density of trichomes were the highest in the bud and tender leaf periods. Further, using the high-throughput sequencing method, we identified 48,856 unigenes, of which 31,574 were differentially expressed. In an analysis of 208 differentially expressed genes (DEGs) encoding transcription factors (TFs), five may involve in trichome development. In addition, on the basis of the Gene Ontolog (GO) annotation and the weighted gene co-expression network analysis (WGCNA) results, we screened several DEGs may contribute to trichome growth, including 66 DEGs related to plant resistance genes (PRGs), 172 DEGs related to cell wall material biosynthesis pathway, 29 DEGs related to cell cycle pathway, and 45 DEGs related to cytoskeleton biosynthesis. Collectively, this study provided high-quality RNA-seq information to improve our understanding of the molecular regulatory mechanism of trichome development and lay a foundation for additional trichome studies in tea plants.